Assessing the degree of innovative readiness of systemic transformation of management in the context of transition to the sixth technological paradigm - N. M. Kalinina; N. A. Kulik (Омский научный вестник: Серия "Общество. История. Современность")
The relevance of the study is due to the need for Russia to actively enter the new post-industrial technological paradigm of the sixth generation, which requires not only an infrastructural basis, but also a scientific and managerial potential. These circumstances, characterized by high rates of change, actualize the tasks of rethinking the value orientations of the management of industrial enterprises, especially in terms of technologies, methods and management tools, focused on the priorities of innovative development, which are reasonably considered as the managerial basis for technological modernization of the economy based on innovative solutions. The purpose of the work is to assess the degree of readiness for the transformation of management systems in the context of the transition to the sixth technological paradigm in the context of studying the innovative activity of industrial entities in the field of developed production technologies, including integrated management and control (advanced methods of organization and production management). The article examines dynamic, structural, trend qualitative variations of the developed advanced production technologies in the Russian Federation for 2000–2021 based on a significant amount of statistical data. The authors concluded that there are positive growth dynamics of developed advanced production technologies, qualitative structural shifts towards Russian developments.